2010
DOI: 10.1021/bi901674q
|View full text |Cite
|
Sign up to set email alerts
|

The Rate-Limiting Catalytic Steps of Hydroxymandelate Synthase from Amycolatopsis orientalis

Abstract: Hydroxymandelate synthase (HMS) catalyzes the committed step in the formation of p-hydroxyphenylglycine, a recurrent substructure of polycyclic nonribosomal peptide antibiotics such as vancomycin. HMS has the same structural fold as and uses the same substrates as 4-hydroxyphenylpyruvate dioxygenase (HPPD) (4-hydroxyphenylpyruvate (HPP) and O(2)). Moreover, HMS catalyzes a very similar dioxygenation reaction to that of HPPD, adding the second oxygen atom to the benzylic position, rather than the aromatic C1 ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 33 publications
0
35
0
Order By: Relevance
“…Surprisingly, no substrate isotope effect was observed when HPP's benzylic hydrogens were substituted with deuteriums, despite the fact that hydrogen abstraction at this position is a catalytic requirement. A solvent isotope effect of 3.5, however, was observed on the rate-limiting final phase that was confirmed by chemical quench and HPLC analysis to be product release, and a proton inventory suggested the contribution of a single proton by the solvent environment to aid this process [96].…”
Section: Two-substrate α-Keto Acid Dependent Oxygenase Family: Hppd Amentioning
confidence: 87%
See 2 more Smart Citations
“…Surprisingly, no substrate isotope effect was observed when HPP's benzylic hydrogens were substituted with deuteriums, despite the fact that hydrogen abstraction at this position is a catalytic requirement. A solvent isotope effect of 3.5, however, was observed on the rate-limiting final phase that was confirmed by chemical quench and HPLC analysis to be product release, and a proton inventory suggested the contribution of a single proton by the solvent environment to aid this process [96].…”
Section: Two-substrate α-Keto Acid Dependent Oxygenase Family: Hppd Amentioning
confidence: 87%
“…HPPD and HMS share as much as 35% identity and 50% similarity in their primary sequence [71], but carry out distinct transformations of the common substrate HPP with extremely low error rates for making the product of the other enzyme [96]. The proposed mechanisms for these two enzymes within the framework of the αKAOs consist of ordered substrate binding, oxidative decarboxylation, hydroxylation, and ordered product release as shown in Scheme 4 [97].…”
Section: Two-substrate α-Keto Acid Dependent Oxygenase Family: Hppd Amentioning
confidence: 99%
See 1 more Smart Citation
“…14,18,19 Results of steady-state kinetics measurements indicated that HPP binds to Fe(II) prior to dioxygen, while CO 2 is the first product released from the active site, similarly to other α-keto acid dependent enzymes. [20][21][22] Respail and co-workers performed QM/MM calculations to test the possible binding modes of HPP in the HPPD active site. 23 Different models, created for an Arabidopsis thaliana HPPD structure (PDB code: 1SQD), were employed, including models of the EFe(II)-HPP and E-Fe(IV)=O-HPA complexes.…”
Section: Hmsmentioning
confidence: 99%
“…Taken together, these studies highlight the importance of the interaction of protein and substrate structure for an efficient, site directed oxygenation reaction. The structure of Hms from A. orientalis has been solved [10] and based on kinetic analyses, which have revealed a lack of kinetic isotope effects on the turnover number, it has recently been concluded that product release is the rate limiting step regarding the conversion of the native substrate, HPP, by A. orientalis Hms [11].…”
Section: Introductionmentioning
confidence: 99%